Lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon and application of lithium-oxygen battery catalyst
By carbonizing activated sludge and acid modifying, N and O doping carbon materials are prepared. As the positive electrode material of lithium oxygen batteries, the problems of poor circulation performance and high cost of lithium oxygen batteries are solved, and the effects of improving battery performance and reducing cost are achieved.
Patent Information
- Application Number
- CN202510378359.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Lithium oxygen batteries have low energy efficiency, short cycle life and poor rate performance. The existing methods for preparing positive electrode materials are complex and costly.
By carbonizing and acid modifying the remaining activated sludge in the city, a carbon material rich in N and O doping was prepared, which was used as the positive electrode material for lithium oxygen batteries and applied to the gas diffusion layer.
It significantly improves the circulation performance of lithium oxygen batteries, extends the cycle life of the battery, and achieves large-scale production at low cost, filling the gap in activated sludge in lithium oxygen batteries applications.
Smart Images

Figure CN119890329A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials for lithium oxygen batteries, and in particular relates to a lithium oxygen battery catalyst prepared based on activated sludge biomass carbon and application thereof. Background Art
[0002] The increasingly serious environmental problems and energy crisis have prompted researchers to explore efficient electrochemical energy storage and conversion devices. Secondary batteries have become one of the answers to these problems, such as lithium-ion batteries, lithium-sulfur batteries, fuel cells, etc. Among them, lithium-oxygen batteries have been favored by scientific researchers because of their ultra-high theoretical capacity. The theoretical capacity of lithium-oxygen batteries is as high as 11140 Wh / Kg, which is close to the energy density of petroleum (13000 Wh / Kg). It is one of the most promising energy storage and conversion devices. However, there are also the following problems: low energy efficiency, short cycle life and poor rate performance. The positive electrode is an indispensable component in lithium-oxygen batteries. The catalytic reaction of the electrode mainly occurs at the solid-liquid-gas three-phase interface between the catalytic active substance, the electrolyte and oxygen. The factors on the three-phase interface affect the discharge capacity, rate and cycle performance of the battery. Therefore, it is very necessary to develop a reliable positive electrode material. At present, the commonly used materials for lithium-oxygen batteries mainly include the following: carbon materials, precious metals, and transition metal-oxygen materials. Carbon materials are widely used as positive electrode materials due to their large specific surface area, good oxygen reduction activity, suitable pore size and volume, porous positive electrode that can promote the transfer of oxygen, electrons and lithium ions, and economic advantages. However, different carbon materials will undergo carbon corrosion to varying degrees, and the generation of carbon corrosion side reactions will lead to a decrease in the cycle performance of lithium-oxygen batteries. The electrocatalytic activity of carbon materials can be improved by element doping of carbon materials, and the cycle performance of lithium-oxygen batteries can be improved. Biomass materials can be used to prepare nitrogen-doped carbon because the protein in them contains nitrogen atoms. This method can be used to mass-produce nitrogen-doped carbon at low cost. In the prior art, biomass carbon materials are also used for carbon-based negative electrode materials for lithium batteries, but potassium, calcium, sodium, magnesium, aluminum, zinc, titanium and cast aluminum alloy powder need to be added during the preparation process. The strong reducing properties of metal magnesium, aluminum, zinc and titanium are used to preferentially react with a large number of oxygen-containing functional groups in biomass, reduce the loss of carbon source, improve carbon conversion rate and reduce defects in carbon materials. In addition, the local reaction of metal magnesium, aluminum, zinc, titanium and oxygen-containing functional groups will release a large amount of heat, and the high temperature and high pressure reaction environment will increase the local graphitization degree and enhance the conductivity of the material. However, its preparation method is complicated and the cost is high.
[0003] Against the background of continuous advancement of urban construction and development, the amount of municipal sewage treated has gradually increased, among which the activated sludge method has become the main technology for treating municipal sewage. However, the problem of treating excess activated sludge has become increasingly prominent and has become a challenge that must be taken seriously. The commonly used treatment methods for excess activated sludge currently include sanitary landfill, sludge incineration, and land resource utilization. In the prior art, there are also methods for resource utilization of activated sludge, but most of them are applied in the field of photocatalysis, such as mixing n-butyl titanate with activated sludge carbon particles, calcining, using activated sludge carbon particles as a carrier, and coating the carrier with titanium dioxide to prepare a loaded photocatalyst, which can effectively remove heavy metals in sewage.
[0004] If the remaining activated sludge can be carbonized, the nitrogen and organic matter it contains can be effectively recovered, and it can be further converted into the positive electrode material of lithium-oxygen batteries, it can not only solve the problem of remaining activated sludge to a certain extent, but also realize the recycling of resources.
[0005] At present, there is no report on the application of residual activated sludge in lithium-oxygen batteries. Summary of the invention
[0006] In order to solve the above-mentioned technical problems, one of the purposes of the present invention is to provide a lithium-oxygen battery catalyst based on activated sludge biomass carbon prepared by utilizing urban residual activated sludge, and applying it to the gas diffusion layer of the lithium-oxygen battery can significantly improve the cycle performance of the lithium-oxygen battery and extend the battery cycle life.
[0007] To achieve the above-mentioned purpose of the invention, the technical solution adopted by the present invention is: a lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon, wherein the lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon is acid-modified activated sludge biomass carbon, and the preparation method comprises the following steps: Sedimentation: Add deionized water to the activated sludge, and after sedimentation, take the mixed solution in the middle layer to obtain activated sludge I; Cleaning and purification: Add low concentration acid to activated sludge I for cleaning and purification to obtain activated sludge II; Drying: freeze-drying the activated sludge II to obtain activated sludge III; Calcination: Place activated sludge III in a tubular furnace and calcine under nitrogen protection to obtain activated sludge biomass carbon; Acid modification: The obtained activated sludge biomass carbon is added to a high concentration of acid, soaked, and washed to obtain acid-modified activated sludge biomass carbon.
[0008] Furthermore, in the sedimentation step, according to the material-liquid ratio, activated sludge: deionized water = 1 g: (50-150) mL, and the sedimentation is 10 min-30 min.
[0009] Furthermore, in the cleaning and purification step, the low-concentration acid is selected from hydrochloric acid, nitric acid or sulfuric acid.
[0010] Furthermore, a low concentration of acid is used, wherein the acid concentration is 1% to 5% by volume.
[0011] Furthermore, in the calcination step, the calcination is carried out at 700°C-900°C for 4 h-5 h.
[0012] Furthermore, in the acid modification step, the high-concentration acid is selected from nitric acid, hydrochloric acid or sulfuric acid.
[0013] Furthermore, a high concentration of acid is used, wherein the acid concentration is 30%-50% by volume.
[0014] Furthermore, in the acid modification step, the soaking time is 5 h-7 h.
[0015] The second purpose of the present invention is to provide an application of a lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon, and to apply the lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon as a positive electrode material to a lithium-oxygen battery.
[0016] Furthermore, the acid-modified activated sludge biomass carbon and the binder are dissolved in nitrogen-methylpyrrolidone, ultrasonicated for 60 min-120 min, and the resulting slurry is drop-coated on a carrier of a gas diffusion layer and dried at 100 ℃-120 ℃ for 12 h-14 h to obtain a positive electrode sheet for a lithium-oxygen battery.
[0017] Furthermore, the binder is polyvinylidene fluoride.
[0018] Further, by mass ratio, acid-modified activated sludge biomass carbon: polyvinylidene fluoride = (8-9): (2-1).
[0019] The beneficial effects of the present invention are: The electrocatalytic activity of carbon materials can be improved by doping them with elements. The lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon proposed in the present invention is prepared by recycling activated sludge to carbonize it, then immersing the activated sludge biomass carbon in a high-concentration acid solution, and finally washing it several times to remove the acid. Since the protein in the activated sludge contains nitrogen atoms, a carbon material rich in N and O doping is obtained. The obtained acid-modified activated sludge biomass carbon obtains a larger specific surface area and oxygen defect introduction, thereby optimizing and improving the cycle performance of the lithium-oxygen battery. The method of the present invention can be used to mass-produce nitrogen-doped carbon at a low cost. The present invention fills the gap in the application of activated sludge in lithium-oxygen batteries. The operation is simple and effective, and activated sludge can be effectively utilized. The prepared carbon material has good cycle stability, which provides a technical basis for the research and development of positive electrode materials for lithium-oxygen batteries and the resource utilization of activated sludge. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 The SEM images, XRD images and EDS spectra of acid-modified activated sludge biomass carbon obtained at different soaking times are shown in Figure 1. Figure 1 a is the SEM image of activated sludge biomass carbon without acid modification after immersion for 0 h; Figure 1 b is the SEM image of the acid-modified activated sludge biomass carbon obtained after immersion for 3 h; Figure 1 c is the XRD pattern of acid-modified activated sludge biomass carbon with different soaking times; Figure 1 d is the SEM image of the acid-modified activated sludge biomass carbon obtained after immersion for 6 h; Figure 1 e is the SEM image of the acid-modified activated sludge biomass carbon obtained after immersion for 9 h; Figure 1 f is the EDS spectrum of acid-modified activated sludge biomass carbon obtained after immersion for 6 h.
[0022] Figure 2 is the CV diagram of acid-modified activated sludge biomass carbon obtained at different soaking times.
[0023] Figure 3 This is the cycle life diagram of lithium-oxygen battery using acid-modified activated sludge biomass carbon as positive electrode material prepared by immersion for 6 h. DETAILED DESCRIPTION
[0024] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In a first aspect of an embodiment of the present invention, a lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon is provided. The lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon is acid-modified activated sludge biomass carbon. The preparation method comprises the following steps: Sedimentation: Add deionized water to the activated sludge, and after sedimentation, take the mixed solution in the middle layer to obtain activated sludge I; Cleaning and purification: Add low concentration acid to activated sludge I for cleaning and purification to obtain activated sludge II; Drying: freeze-drying the activated sludge II to obtain activated sludge III; Calcination: Place activated sludge III in a tubular furnace and calcine under nitrogen protection to obtain activated sludge biomass carbon; Acid modification: The obtained activated sludge biomass carbon is added to a high concentration of acid, soaked, and washed to obtain acid-modified activated sludge biomass carbon.
[0026] The electrocatalytic activity of carbon materials can be improved by doping carbon materials with elements. The present invention proposes a method for resource utilization of activated sludge. Since the protein in the activated sludge contains nitrogen atoms, nitrogen-doped carbon is prepared by carbonization and acidification modification. The present invention can use this method to mass-produce nitrogen-doped carbon at a low cost. The present invention uses residual activated sludge as a recycled material for carbonization and acidification modification. The residual activated sludge is washed and purified multiple times and then placed in a freeze dryer for drying overnight. Next, the purified activated sludge powder is placed in a tubular furnace and calcined under nitrogen protection. The prepared material is placed in a mixed solution of water and acid for immersion and acid modification to obtain a carbon material rich in N and O doping, and a larger specific surface area and oxygen defect introduction are obtained. It is applied to lithium-oxygen batteries to optimize and improve the cycle performance of lithium-oxygen batteries.
[0027] In some feasible implementations, in the sedimentation step, the solid-liquid ratio is activated sludge: deionized water = 1 g: (50-150) mL, and the sedimentation is 10 min-30 min.
[0028] Specifically, the aged activated sludge has a faster settling speed and contains more impurities. The activated sludge in the middle layer of the present invention is relatively clean and has better activity. In addition, by controlling the solid-liquid ratio, activated sludge: deionized water = 1 g: (50-150) mL, and settling for 10 min-30 min, a balance between settling efficiency and settling effect is achieved.
[0029] In some feasible embodiments, in the cleaning and purification step, the low-concentration acid is selected from hydrochloric acid, nitric acid or sulfuric acid. Furthermore, the low-concentration acid is used, and the concentration of the acid is 1%-5% by volume.
[0030] The present invention can remove some metal salt impurities in the activated sludge through low-concentration acid washing, where the acid concentration is 1%-5% by volume, so as to make the activated sludge relatively pure, and the use of low-concentration acid washing can largely not change the carbon component in the activated sludge.
[0031] Furthermore, in the calcination step, the calcination is carried out at 700°C-900°C for 4 h-5 h.
[0032] In the present invention, when the calcination temperature is lower than 700°C, the graphite nitrogen ratio of nitrogen in the activated sludge is low, and the catalytic activity will be affected. When the calcination temperature is higher than 900°C, it will lead to compact sintering, thereby reducing the porosity.
[0033] In some feasible embodiments, in the acid modification step, the high concentration acid is selected from nitric acid, hydrochloric acid or sulfuric acid. Furthermore, the high concentration acid is used, and the acid concentration is 30%-50% by volume. Furthermore, in the acid modification step, the soaking time is 5 h-7 h.
[0034] Specifically, since the surface of activated sludge biomass carbon tends to adsorb various impurities (such as ash, oxides, metal ions, etc.), high concentrations of acid have strong dissolving power and can effectively remove these impurities. High concentration acid treatment can not only clean the surface of activated sludge biomass carbon, but also change its surface microstructure and increase porosity. High concentrations of acid can introduce oxygen groups, change the electronic structure of activated sludge biomass carbon, and optimize its conductive properties. Optionally, the high concentration of acid is nitric acid, hydrochloric acid or sulfuric acid, and the concentration of the acid is 30%-50% by volume; preferably, the high concentration of acid is nitric acid, and the concentration of the acid is 50% by volume. If the soaking time is too short, the high concentration of acid will not have enough time to react with the carbon surface, and it will not be possible to completely remove impurities or introduce enough functional groups, resulting in unsatisfactory modification effects; if the soaking time is too long, the high concentration of acid will react with the carbon surface undesirably, causing degradation of material properties, and may even cause the shedding of certain functional groups or structural changes. Preferably, the soaking time is 5 h-7 h; more preferably, the soaking time is 6 h.
[0035] A second aspect of an embodiment of the present invention provides an application of a lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon, and applies the lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon as a positive electrode material to a lithium-oxygen battery.
[0036] Optionally, the preparation method of the positive electrode sheet of the lithium oxygen battery is to dissolve the acid-modified activated sludge biomass carbon and the binder in nitrogen methyl pyrrolidone, ultrasonicate for 60 min-120 min, drop-coat the obtained slurry on the carrier of the gas diffusion layer, and dry at 100 ℃-120 ℃ for 12 h-14 h to obtain the positive electrode sheet of the lithium oxygen battery. Preferably, the binder is polyvinylidene fluoride. Preferably, by mass ratio, acid-modified activated sludge biomass carbon: polyvinylidene fluoride = (8-9): (2-1).
[0037] The acid-modified activated sludge biomass carbon provided by the present invention is a N and O-doped carbon material with a larger specific surface area and the introduction of oxygen defects. The application of the acid-modified activated sludge biomass carbon to the positive electrode of a lithium-oxygen battery can improve the electrocatalytic activity of the carbon material and extend the battery cycle life.
[0038] 1. Method selection 1. The method is as follows: 1) Settlement: Weigh 10 g of activated sludge, add 1000 mL of deionized water, stir evenly, and after settling for 20 min, take the middle layer mixed solution to obtain activated sludge I.
[0039] 2) Cleaning and purification: According to the volume ratio, activated sludge I: hydrochloric acid = 1:50, hydrochloric acid with a volume percentage concentration of 5% was added to the activated sludge I for washing and purification to obtain activated sludge II.
[0040] 3) Drying: The activated sludge II is placed in a freeze dryer to remove moisture, and freeze-dried to obtain activated sludge III.
[0041] 4) Calcination: The activated sludge III was placed in a tubular furnace and calcined at 800 °C for 4 h under nitrogen protection to obtain activated sludge biomass carbon.
[0042] 5) Acid modification: The activated sludge biomass carbon obtained in step 4) is soaked in a nitric acid solution having a volume ratio of deionized water to nitric acid of 1:1 for 6 hours to obtain acid-modified activated sludge biomass carbon.
[0043] 6) Lithium oxygen battery assembly: According to the mass ratio, acid-modified activated sludge biomass carbon: polyvinylidene fluoride = 9:1. Take acid-modified activated sludge biomass carbon and polyvinylidene fluoride (PVDF), add appropriate amount of nitrogen methyl pyrrolidone, ultrasonicate for 100 min, mix evenly, and obtain slurry. The slurry is coated on the gas diffusion layer (carbon paper), and the coated gas diffusion layer is placed in an oven at 100 ° C and dried for 12 h. The coated gas diffusion layer is used as the positive electrode of the lithium oxygen battery, the lithium sheet is used as the negative electrode, the diaphragm uses a glass fiber diaphragm (Whatman battery diaphragm), and the electrolyte uses (1 M LiTFSI in TETRAGLYME) to assemble the lithium oxygen battery.
[0044] 2. Performance Testing Comparative example: No acid modification was performed, and the activated sludge biomass carbon obtained in step 4) was directly used. According to the mass ratio, activated sludge biomass carbon: polyvinylidene fluoride = 9:1, activated sludge biomass carbon and polyvinylidene fluoride (PVDF) were taken, nitrogen methyl pyrrolidone was added, ultrasonicated for 100 min, mixed evenly, and slurry was obtained. The slurry was coated on the gas diffusion layer (carbon paper), and the coated gas diffusion layer was placed in an oven at 100 ° C and dried for 12 h. The coated gas diffusion layer was used as the positive electrode of the lithium oxygen battery, the lithium sheet was used as the negative electrode, the diaphragm used a glass fiber diaphragm (Whatman battery diaphragm), and the electrolyte used (1 M LiTFSI in TETRAGLYME) to assemble the lithium oxygen battery.
[0045] The prepared materials were characterized by physical properties and CV tests, and the results were as follows Figure 1 and Figure 2 . Figure 1 and Figure 2 The 0h represented in the figure means that no high concentration acid immersion was carried out, that is, no acid modification was carried out, which corresponds to the comparative example.
[0046] Depend on Figure 1 It can be seen from 0 h (a) and 6 h (d) that after modification with high concentration acid, the fine particles on the surface of the material gradually decreased. Figure 1 The XRD pattern in (c) shows that the carbon peak gradually weakens after high concentration acid modification, which indicates that the introduction of oxygen functional groups after high concentration acid modification may lead to a decrease in in-plane crystallinity. Figure 1 The EDS graph in (f) shows that the acid-modified activated sludge biomass carbon prepared in the present invention is a N and O-doped carbon material.
[0047] from Figure 2 It can be observed from the results that the electrochemical performance of the synthesized materials was tested by cyclic voltammetry (CV) at different scan rates. As the scan rate increases, the CV current of the material gradually increases, indicating that its electrochemical response increases with the increase in the scan rate. Among them, the material modified by immersion in high-concentration nitric acid for 6 h shows the largest CV curve area, which indicates that the material has the most significant electrochemical active area and may show better performance in energy storage or catalytic applications.
[0048] In summary, the present invention preferably performs high-concentration acid modification on activated sludge biomass carbon.
[0049] (II) Screening of soaking time in the acid modification step 1. The method is as follows: 1) Sedimentation: same as the screening method (I) 2) Cleaning and purification: same as the screening method in (I). 3) Drying: Same as the screening method in (I) 4) Calcination: Same as the screening method in (I) 5) Acid modification: The activated sludge biomass carbon obtained in step 4) was respectively put into a nitric acid solution with a volume ratio of deionized water to nitric acid of 1:1, and soaked for 3 h, 6 h and 9 h, respectively, to obtain acid-modified activated sludge biomass carbon with different soaking times.
[0050] 6) Lithium-oxygen battery assembly: same screening as method (I) 2. Performance Testing The prepared materials were characterized by physical properties and CV tests, and the results were as follows Figure 1 and Figure 2 .
[0051] Figure 1 The following are the SEM images, EDS spectra and XRD images of acid-modified activated sludge biomass carbon obtained at different soaking times. Figure 1 It can be seen that the acid-modified activated sludge biomass carbon provided by the present invention introduces nitrogen natural element doping and oxygen functional groups compared to ordinary carbon. As the soaking time in high-concentration nitric acid increases, the surface of the resulting material becomes smoother, the peak width of XRD carbon becomes narrower, and the crystallinity decreases. If the soaking time is too short, the acid will not have enough time to react with the carbon surface, and it will not be possible to completely remove impurities or introduce enough functional groups, resulting in unsatisfactory modification effects. If the soaking time is too long, the acid will have undesirable side reactions with the carbon surface, causing degradation of material properties, and may even cause certain functional groups to fall off or change their structures. Therefore, the present invention preferably soaks for 5 h-7 h.
[0052] Figure 2 The CV graphs of modified activated sludge biomass carbon obtained at different soaking times are shown in FIG. 6 . Among them, the CV area of 6 h is the largest, indicating that it has the largest electrochemical active area. Therefore, the present invention preferably uses a soaking time of 6 h.
[0053] Figure 3 The cycle life of lithium-oxygen battery using acid-modified activated sludge biomass carbon as positive electrode material prepared by soaking for 6 h. Figure 3 It can be seen that the cyclic discharge at 500 mAh / g capacity for 6 h has good cycle stability. The first discharge platform at 0 h is 2.55 V, with a higher overpotential of 1.83 V. The first discharge platform at 6 h is stable at 2.76 V, with a lower overpotential of 1.51 V, and the discharge voltage platform is relatively stable from the 1st cycle to the 50th cycle. The rechargeable battery voltage increases with the number of cycles, which may be due to the Li 2 O 2The incomplete decomposition of the electrolyte leads to a continuous reduction in oxygen and ion transport paths. In addition, the continuous occurrence of side reactions causes carbon corrosion at the positive electrode, which leads to a continuous reduction in active sites. As the reaction continues, the lithium negative electrode may also react with oxygen, resulting in surface passivation. In addition, the decomposition of the electrolyte at high voltage may also be one of the reasons for the decrease in cycle stability.
[0054] (III) Selection of acid in the acid modification step Here’s how: 1) Sedimentation: same as the screening method (I) 2) Cleaning and purification: same as the screening method in (I). 3) Drying: Same as the screening method in (I) 4) Calcination: Same as the screening method in (I) 5) Acid modification: The activated sludge biomass carbon obtained in step 4) was placed in a nitric acid, hydrochloric acid or sulfuric acid solution with a volume ratio of deionized water to acid of 1:1, and after soaking for 6 hours, acid-modified activated sludge biomass carbon with different acid types was obtained. The half-wave potentials of the three acid-modified activated sludge biomass carbon materials after soaking in nitric acid, hydrochloric acid and sulfuric acid, respectively, are shown in Table 1.
[0055] Table 1
[0056] It can be seen from the results in Table 1 that the half-wave potential of the material after immersion in nitric acid is the highest, indicating that it has the best electrocatalytic activity. Therefore, the present invention preferably uses a nitric acid solution (50% by volume concentration) with a volume ratio of deionized water to nitric acid of 1:1 to acid-modify the activated sludge biomass carbon.
[0057] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed. The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application. The above are only preferred implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.
Claims
1. A lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon, characterized in that: The lithium oxygen battery catalyst prepared based on activated sludge biomass carbon is acid-modified activated sludge biomass carbon, and the preparation method comprises the following steps: Sedimentation: Add deionized water to the activated sludge, and after sedimentation, take the mixed solution in the middle layer to obtain activated sludge I; Cleaning and purification: Add low concentration acid to activated sludge I for cleaning and purification to obtain activated sludge II; Drying: freeze-drying the activated sludge II to obtain activated sludge III; Calcination: Place activated sludge III in a tubular furnace and calcine under nitrogen protection to obtain activated sludge biomass carbon; Acid modification: The obtained activated sludge biomass carbon is added to a high concentration of acid, soaked, and washed to obtain acid-modified activated sludge biomass carbon.
2. The lithium oxygen battery catalyst prepared based on activated sludge biomass carbon according to claim 1, characterized in that: In the sedimentation step, according to the material-liquid ratio, activated sludge: deionized water = 1 g: (50-150) mL, sedimentation 10 min-30 min.
3. The lithium oxygen battery catalyst prepared based on activated sludge biomass carbon according to claim 1, characterized in that: In the cleaning and purification step, the low-concentration acid is selected from hydrochloric acid, nitric acid or sulfuric acid; the concentration of the acid is 1%-5% by volume.
4. The lithium oxygen battery catalyst prepared based on activated sludge biomass carbon according to claim 1, characterized in that: In the calcination step, the calcination is carried out at 700°C-900°C for 4 h-5 h.
5. The lithium oxygen battery catalyst prepared based on activated sludge biomass carbon according to claim 1, characterized in that: In the acid modification step, the high-concentration acid is selected from nitric acid, hydrochloric acid or sulfuric acid; the concentration of the acid is 30%-50% by volume.
6. The lithium oxygen battery catalyst prepared based on activated sludge biomass carbon according to claim 5, characterized in that: In the acid modification step, the soaking is performed for 5 h to 7 h.
7. Application of lithium oxygen battery catalyst prepared based on activated sludge biomass carbon, characterized in that: The lithium-oxygen battery catalyst prepared based on activated sludge biomass carbon as described in any one of claims 1 to 6 is applied to a lithium-oxygen battery as a positive electrode material.
8. The use according to claim 7, characterized in that: The acid-modified activated sludge biomass carbon and the binder are dissolved in nitrogen methyl pyrrolidone, ultrasonicated for 60 min-120 min, the obtained slurry is drop-coated on the carrier of the gas diffusion layer, and dried at 100°C-120°C for 12 h-14 h to obtain the positive electrode sheet of the lithium oxygen battery.
9. The use according to claim 8, characterized in that: The binder is polyvinylidene fluoride.
10. The use according to claim 9, characterized in that: By mass ratio, acid-modified activated sludge biomass carbon: polyvinylidene fluoride = (8-9): (2-1).
Citation Information
Patent Citations
Method for preparing carbon nano tube loaded nano nickel powder material by liquid-phase reduction method
CN102161000A
Nitrogen-phosphorus double-doped carbon material as well as preparation method and application thereof
CN106025296A
Preparation method of porous carbon sphere negative electrode material for lithium battery
CN110395728A
Pretreatment method of carbon carrier for battery catalyst and carbon carrier
CN112331862A
Application of biochar material in lithium oxygen battery
CN117913299A